Saga rodu Anisimowiczów - Kosiński, Amilkar (Zeszyty Wiejskie, 2016)
The saga about the Anisimowicz family is a chronicle record of fates of the family coming from Podlasie – current borderland in the east of Poland. For centuries it was a cultural, social and ethnic conglomeration, which was inhabited by Jews, Tartars, Ruses, Byelorussians, Lithuanians and Poles. The story written by Roman Anisimowicz, descendant of the family, dates back to the 18th/19th century. From a perspective of fates of the country, multigenerational family he presents the reality of the life of the Polish province relating to social, economic and political transformations of one area, during nearly two centuries.